Microbiological Assessment of Selected Vegetables from Kathmandu, Nepal (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To determine the microbial load and antibiotic susceptibility of bacterial isolates from selected vegetables in Kathmandu.Method: This study was conducted in the department of microbiology, Tri-Chandra multiple campus from March to July 2025. A total of 30 samples including, moringa, cucumber, spinach, chili, peas, cauliflower, okra, carrot, cabbage, and brinjal, were collected in sterile containers from markets, hotels, and farms and were transported to the laboratory under cold chain. The samples were cultured on Plate Count Agar (PCA), Potato Dextrose Agar (PDA), and Violet Red Bile Agar (VRBA). The PCA and VRBA plates were incubated at 37℃ for 24 hours and PDA plates at 28℃ for 24-48 hours. Bacterial isolates were identified using Gram staining and various biochemical tests, and antibiotic susceptibility was performed. Fungal presence was detected by using Lactophenol Cotton Blue stain and parasites were identified by Wet Mount method.Results: Spinach from vendor had the highest mesophilic bacterial load (1.54×10⁶CFU/g) and lowest on peas from hotels (1.7×103CFU/g). Coliform were highest in vendor cabbage (2.89×10⁵CFU/g), while peas consistently showed lowest counts (5×102CFU/g) from all sources. Bacteria such as Pseudomonas spp., E. coli, Proteus spp., Enterobacter spp, S. aureus, Klebsiella spp, and fungi like Aspergillus spp, Fusarium spp, Alternaria spp, Cladosporium spp, Candida spp, and parasites G. lamblia, E. histolytica, Ascaris were identified. Most of the bacterial isolates were resistant to the antibiotics used, including Ceftriaxone, Cotrimoxazole, Ceftazidime, Amikacin, Erythromycin, and Ciprofloxacin with only few exhibiting susceptibility.Conclusion: The study revealed a significant presence of pathogens and antibiotic resistant strains highlighting the importance of improved food safety practices, regular microbial monitoring, and public awareness to reduce the risk of foodborne diseases in urban Nepal.